Self Disclosure Analysis of Second Instagram Account Users Among Students of Dehasen University Bengkulu - Bogi Andrian; Anis Endang SM; Vethy Octaviani (Penerbit Jurnal Indonesia, 2022)
This study aims to find out the self disclosure of second instagram account users among students of Dehasen Bengkulu University. In this study using qualitative research methods with a type of qualitative descriptive approach research. The number of informants in this study was 5 people. Data collection techniques in this study used methods of observation, interview and documentation. The data analysis technique performed is a Miles and Huberman model analysis technique that is carried out in three stages, data reduction, data presentation and drawing conclusions or verification. The results showed the expression made by informants to channel hobbies, entertain themselves, and let go of the unek-unek. Self-clarity, at this stage the post that the informant shared on the second account about a person who is liked and also about life problems. Social control, this stage all informants prefer to hide personal information. In the development of relationships, it can be said that not all informants have been in contact with friends on second accounts.